Urothelial cell carcinoma of the bladder in pediatric patients: a systematic review and data analysis of the world literature. Issue 4 (August 2019) - Rezaee, M.E.; Dunaway, C.M.; Baker, M.L.; Penna, F.J.; Chavez, D.R.
Summary: Background: Urothelial cell carcinoma (UCC) of the bladder is exceedingly rare in pediatric patients. Limited data are available to guide management in this population. Methods: The authors systematically searched MEDLINE, Cochrane Library, and Google Scholar (through February 2019) for case reports and series to summarize data regarding presentation, evaluation, management, and follow-up for patients ≤ 18 years diagnosed with UCC of the bladder. Patient-level data were abstracted, and adjusted logistic regression was used to identify factors associated with a combined outcome of recurrence or death. Results: One hundred two articles describing 243 patients from 26 countries met criteria. Average age was 12.5 years, 32.6% were female, 15.3% had medical comorbidities, and 13.2% had known risk factors for bladder cancer. Initial management was transurethral resection in 95.5% of patients, whereas 6.2% required secondary intervention. Tumor stage was TaN0M0 in 86.4% and low grade in 93.4%. Recurrence and death occurred in 8.6% and 3.7%, respectively. Mean time to recurrence or death was 8.6 months (standard deviation [SD] 7.6) for 10.7%. Mean disease free follow-up without recurrence or death was 56.9 months (SD 54.2) for 89.3%. Patients with comorbidities, risk factors, or family history (odds ratio [OR]: 2.4, 95% confidence interval [CI]: 1.02–5.6); ≥TaN0M0 disease (OR: 6.2, 95% CI: 2.5–15.6); and larger tumors at diagnosis (OR: 1.7, 95% CI: 1.2–2.4) had significantly greater adjusted odds of recurrence or death after initial treatment. Conclusion: Based on pooled results, disease recurrence or death occurred in 10.7% of pediatric patients and within 9 months for most and within 32 months for all patients. This may suggest that low-grade and stage UCC of the bladder in pediatric patients can be systematically monitored for at least 3 years. However, prospective evaluation of this clinical strategy is warranted.